Microbial communities and volatile profile of Queijo de Azeitão PDO cheese, a traditional Mediterranean thistle-curdled cheese from Portugal. (September 2021) - Cardinali, Federica; Ferrocino, Ilario; Milanović, Vesna; Belleggia, Luca; Corvaglia, Maria Rita; Garofalo, Cristiana; Foligni, Roberta; Mannozzi, Cinzia; Mozzon, Massimo; Cocolin, Luca; Osimani, Andrea; Aquilanti, Lucia
Graphical abstract: Highlights: Microbial communities of Queijo de Azeitão PDO cheese were studied. Leu . mesenteroides, L . lactis, Lcb . zeae, Len . kefiri were majority in all samples. Mycobiota composition showed the neat dominance of Y . lipolytica . Twenty-four different volatile compounds were identified. Len . kefiri was detected in Queijo de Azeitão PDO cheese for the first time. Abstract: The production of ovine or caprine milk cheeses with thistle rennet is a common practice in the Mediterranean basin. The aim of the present study was to obtain information on bacteria and yeast communities harboured by Queijo de Azeitão PDO cheese through viable counting and, for the first time, via metataxonomic analysis. Moreover, solid phase microextraction (SPME) technique was applied to characterize Queijo de Azeitão PDO cheese volatile compounds. Nine cheese samples were collected from three different artisan producers located in Portugal. The results of physico-chemical analyses showed significant differences between producers, with mean values ranging from 5.40 ± 0.25 (Producer 1) to 6.00 ± 0.22 (Producer 2). As for TTA, Producer 1 showed the highest mean value attesting at 18.04 ± 6.57 mL of 0.1 M NaOH used to reach pH 8.3. Regarding lactic acid concentration, Producer 1 showed the highest mean value attesting at 0.488 ± 0.106 g 100 g −1, whereas, for acetic acid, no significant differences were evidenced among producers with values comprised between 0.141 ± 0.021 g 100 g −1 and 0.245 ± 0.016 g 100 g −1 . No significant differences were observed between overall mean values of the three producers for viable counts of presumptive lactococci, thermophilic cocci, presumptive lactobacilli, thermophilic lactobacilli and total mesophilic aerobes with values in the order of 7–8 log cfu g −1 . Moreover, no significant differences were evidenced for viable counts of coagulase-negative cocci, enterococci, Enterobacteriaceae and Pseudomonadaceae . As for eumycetes, cheeses from Producer 1 showed the lowest mean value (2.78 ± 2.42 log cfu g −1 ) in respect with values detected in cheeses from Producer 2 and 3. Concerning microbiota and mycobiota of the analyzed cheeses, the alpha diversity index did not show any significant difference between the three producers in terms of composition and complexity of the microbial population. A simple composition was apparently shared by the three producers, whose cheese manufactures were dominated by the presence of Leuconostoc mesenteroides (37% of the relative frequency in average), Lactococcus lactis (29%), Lacticaseibacillus zeae (4.7%), Lentilactobacillus kefiri (4.4%), Serratia spp. (3.5%), Lactiplantibacillus plantarum (2.7%), and Latilactobacillus sakei (2.5%). The mycobiota composition showed the neat dominance of Yarrowia lipolytica (46.7% of the relative frequency in average), followed by Candida ethanolica (13.6%), Kurtzmaniella zeylanoides (9.4%), Geotrichum candidum (8.8%), Galactomyces geotrichum (8.7%), Kluyveromyces lactis (3.5%), and Geotrichum silvicola (2.7%). The volatile profile analysis allowed 24 different compounds to be identified: 7 acids, 7 esters, 4 alcohols, 3 ketones, 2 aromatic hydrocarbons, and 1 aldehyde. The most represented volatile organic compounds (VOCs) were 2-butanone, butanoic acid and hexanoic acid. A positive correlation between Len. kefiri and hexanoic acid and isopentyl isobutyrate was observed ( P < 0.05), whereas Y. lipolytica displayed the highest number of positive correlations with 3-methyl-butanal, 2-pentanone and 2-pentanol (P < 0.05). To the authors' knowledge, this is the very first detection of Len. kefiri in a raw ewe's milk cheese coagulated with vegetable rennet.